The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/aps.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of octacosanol on 6-hydroxydopamine-induced Parkinsonism in rats via regulation of ProNGF and NGF signaling

Abstract: Aim: To investigate the protective effects of octacosanol in 6-hydroxydopamine-induced Parkinsonian rats and find whether octacosanol has effects on pro nerve growth factor (pro-NGF), NGF and the downstream effector proteins. Methods: Behavioral tests, enzymatic assay, tyrosine hydroxylase immunohistochemistry, TUNEL and Western blot were used to investigate the effects of octacosanol in this rat model of PD. Results: Oral administration of octacosanol (35-70 mg/kg, po for 14 d) significantly improved the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 55 publications
(63 reference statements)
0
30
0
1
Order By: Relevance
“…6-OHDA is a neurotoxin that induces the specific degeneration of DA neurons and is usually used to prepare PD animal models [35] . It has been reported that 6-OHDA produces reactive oxygen species (ROS) and impairs mitochondrial function [36] .…”
Section: Discussionmentioning
confidence: 99%
“…6-OHDA is a neurotoxin that induces the specific degeneration of DA neurons and is usually used to prepare PD animal models [35] . It has been reported that 6-OHDA produces reactive oxygen species (ROS) and impairs mitochondrial function [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have shown that octacosanol possessed cholesterol-lowering, antiaggregatory, cytoprotective, ergogenic, neurological, antioxidant properties and protective effects on parkinsonism (Oliaro-Bosso et al, 2009;Taylor et al, 2003;Wang et al, 2010). Long-term clinical studies have demonstrated that, octacosanol was welltolerated and safe (Irmak, Dunford, & Milligan, 2006), and a number of dietary supplements containing octacosanol are commercially available in the US market (Irmak et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…NGF regulates the survival, growth, and differentiation of neurons through multiple mechanisms, especially via activating PI3K/Akt and Raf/MEK/ERK pathways [40]. It is possible that natural or synthetic small molecules elicit the neuroprotective and neurotrophic activities by targeting NGF signals [12,41]. For example, these compounds induce the activation of the prosurvival PI3K/Akt and ERK1/2 signaling pathways [14].…”
Section: Discussionmentioning
confidence: 99%